1999
DOI: 10.1080/02724939992464
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes to HIV/AIDS of senior secondary school pupils and trainee teachers in Udupi District, Karnataka, India

Abstract: A cross-sectional descriptive study using a questionnaire with mostly closed-ended questions was carried out on 990 pupils and 46 trainee teachers to investigate their knowledge of and attitudes to HIV/AIDS. Pupils in one school were reassessed after a health talk and distribution of a handout. Despite having had no formal sex education, most respondents were reasonably well informed about the transmission of HIV. However, there were many misconceptions about transmission and prevention and 16.9% of pupils wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 3 publications
10
26
0
Order By: Relevance
“…11 Study findings reveled those pupils who were reassessed after receiving a talk and handout showed significant improvement in their knowledge and a change in attitude regarding HIV/AIDS. 12 According to areas of HIV/AIDS findings was consistent with result that knowledge scores during pretest the highest mean score (35.75) was 62.71% of the total score was observed on the area of "transmission of HIV-AIDS. 6 Other study result stated that the majority of students had accurate knowledge about HIV/AIDS modes of transmission, with 67-96% correctly answering each of questions.…”
supporting
confidence: 74%
“…11 Study findings reveled those pupils who were reassessed after receiving a talk and handout showed significant improvement in their knowledge and a change in attitude regarding HIV/AIDS. 12 According to areas of HIV/AIDS findings was consistent with result that knowledge scores during pretest the highest mean score (35.75) was 62.71% of the total score was observed on the area of "transmission of HIV-AIDS. 6 Other study result stated that the majority of students had accurate knowledge about HIV/AIDS modes of transmission, with 67-96% correctly answering each of questions.…”
supporting
confidence: 74%
“…HIV-related stigma and discrimination remains an enormous barrier to effectively fighting the HIV and AIDS epidemic. Stigma and discrimination can result in people living with HIV/ AIDS (PLWHA) being shunned by family and the community, poor treatment in healthcare and educational settings, an erosion of rights, and psychological damage [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our study has also noted a number of misconceptions about the cause of HIV/AIDS, including evil spirit, mosquito bites, shaking hands with HIV infected person, living in the same house HIV infected person, sharing the same bed with HIV infected person, sharing food with a person suffering from HIV/AIDS, using public toilet, hugging HIV infected persons, being in a place where infected persons is sneezing and coughing, and studying in the same classroom with HIV person, common among the students studied which are counter productive in the care and support of HIV/AIDS victims. Previous studies have also identified these misconceptions 7,13,21,22 . These misconceptions and the finding that as many as 96.6% of the students studied still believe that HIV/AIDS cannot be cured and as many as 62.7% believing that people living with the disease can never live good lives raise questions as to the effectiveness of the various educational programmes on HIV in Nigeria where huge sums of money has been spent 10 .…”
Section: Discussionmentioning
confidence: 99%